The Microbial Community Dynamics during the Vitex Honey Ripening Process in the Honeycomb - Wen, Yaqin; Wang, Lin; Jin, Yue; Zhang, Jinzhen; Su, Lei; Zhang, Xiaoling; Zhou, Jinhui; Li, Yi (Frontiers in Microbiology, 2017)
The bacterial and fungal communities of vitex honey were surveyed by sequencing the 16S rRNA gene and the internal transcribed spacer region of ribosomal DNA. Vitex honey samples were analyzed at different stage of ripening; the vitex flower was also analyzed, and the effect of the chemical composition in the experimental setup was assessed. The results confirmed the presence of dominant Bacillus spp. as the dominant bacterial in honey, and yeast related genera was the main fungal in the honey, respectively. Lactococcus and Enterococcus were detected for the first time in honey. The proportion of most of the fungal community decreased during the honey ripening process. Multivariate analyses also showed that the fungal community of 5, 10 and 15 d honey samples tended to cluster together and were completely separated from the 1 d honey sample. The change in the fungal community showed a correlation with the variation in the chemical components, such as moisture and phenolic compounds. Together, these results suggest that ripening of honey could change its microbial composition, and decrease the potential risk of microbiology.